2018
DOI: 10.1002/advs.201800064
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress on Layered Double Hydroxides and Their Derivatives for Electrocatalytic Water Splitting

Abstract: Layered double hydroxide (LDH)‐based materials have attracted widespread attention in various applications due to their unique layered structure with high specific surface area and unique electron distribution, resulting in a good electrocatalytic performance. Moreover, the existence of multiple metal cations invests a flexible tunability in the host layers; the unique intercalation characteristics lead to flexible ion exchange and exfoliation. Thus, their electrocatalytic performance can be tuned by regulatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
339
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 572 publications
(369 citation statements)
references
References 183 publications
6
339
1
2
Order By: Relevance
“…It has been reported that the electrochemical activity of LDHs is greatly dependent on the geometric structure and dispersion state, which have significant influence on the electronic properties of active sites . From this view of point, constructing LDH‐INEs with controllable morphology and components is crucial required.…”
Section: Ldh‐inesmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that the electrochemical activity of LDHs is greatly dependent on the geometric structure and dispersion state, which have significant influence on the electronic properties of active sites . From this view of point, constructing LDH‐INEs with controllable morphology and components is crucial required.…”
Section: Ldh‐inesmentioning
confidence: 99%
“…The tunable types of M 2+ , M 3+ , and A n− , and the various molar ratio of M 2+ /M 3+ , lead to a huge variety of LDHs with versatile physical and chemical properties. LDHs have received broad interests as promising electrode materials for batteries, electrocatalysis, biosensors, and supercapacitors since last century owing to their superior physicochemical properties such as large surface area, suitable mesopore distributions, and tunable structure . In the past two decades, the research about LDHs has seen much progress, as evidenced by the rapidly increasing number of publications and citations on this subject, which further demonstrating the high importance and potential value of LDHs (Figure b,c).…”
Section: Introductionmentioning
confidence: 99%
“…Over the past few decades, advanced electrocatalysts for HER have received extensive attentions, due to exhaustible fossil fuels and the rapid growth of energy consumption. Transition metals and their oxides, hydroxides, chalcogenides, phosphides, and nitrides have been reported as promising electrocatalysts to replace noble metals, featured with high activity and earth abundance. Among the candidates, some semiconducting transition metal dichalcogenide (TMDC) materials (e.g., MoS 2 , MoSe 2 , etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Transition‐metal‐based materials, such as hydroxides, oxides, oxyhydroxides, sulfides, and phosphides, are the most studied catalysts for OER and HER . Recent experimental and theoretical analyses have shown that iron‐based Ni‐ and Co‐layered double hydroxides (LDHs), and oxyhydroxides are the best active catalysts for OER in an alkaline medium, owing to the most‐optimal MO bond strength (OER intermediates, e.g., MOH, MO, MOOH, and MOO) . They demonstrated unprecedented catalytic activity for the OER as well as the HER.…”
Section: Introductionmentioning
confidence: 99%
“…They demonstrated unprecedented catalytic activity for the OER as well as the HER. The high activity has attributed to the synergistic effect of “Ni/Co” and “Fe,” where “Fe” doping can improve the conductivity and provide more active sites for OER and HER . Boettcher and co‐workers studies showed that the conductivity of β‐Ni(OH) 2 was increased more than 30‐fold upon “Fe” addition, and the higher activity of β‐Ni 1‐ x Fe x (OH) 2 can be ascribed to the partial charge transfer between “Ni” and “Fe.” Goddard and co‐workers' theoretical studies showed that Fe 4+ and Ni 4+ both play a crucial role on OER in Ni 1‐ x Fe x OOH; they claim that high spin d 4 Fe 4+ stabilizes the O* formation on the MO bond, while the subsequent OO bond formation is catalyzed on low spin d 6 Ni 4+ , making Ni 1‐ x Fe x OOH a much better OER catalyst than NiOOH, where O* is not adequately stabilized .…”
Section: Introductionmentioning
confidence: 99%